2012
DOI: 10.1016/j.bone.2011.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Yellow-bellied Marmots (Marmota flaviventris) preserve bone strength and microstructure during hibernation

Abstract: Reduced skeletal loading typically results in decreased bone strength and increased fracture risk for humans and many other animals. Previous studies have shown bears are able to prevent bone loss during the disuse that occurs during hibernation. Studies with smaller hibernators, which arouse intermittently during hibernation, show that they may lose bone at the microstructural level. These small hibernators, like bats and squirrels, do not utilize intracortical remodeling. However, slightly larger mammals lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 37 publications
(61 reference statements)
2
32
0
Order By: Relevance
“…Hibernators face the risk of losing bone strength during prolonged periods of inactivity. Recent studies in thirteen-lined and golden-mantled ground squirrels, marmots, and woodchucks have shown that some microstructural bone loss occurs during hibernation but macrostructural strength is maintained (24,55,92,100). During hibernation, the osteocyte lacunar porosity increases, indicating a decrease in cell number.…”
Section: Discussionmentioning
confidence: 99%
“…Hibernators face the risk of losing bone strength during prolonged periods of inactivity. Recent studies in thirteen-lined and golden-mantled ground squirrels, marmots, and woodchucks have shown that some microstructural bone loss occurs during hibernation but macrostructural strength is maintained (24,55,92,100). During hibernation, the osteocyte lacunar porosity increases, indicating a decrease in cell number.…”
Section: Discussionmentioning
confidence: 99%
“…This applies to many species, such as bears, squirrels, woodchucks, bats, hamsters, prairie dogs and marmots (Cotton, 2016;Cotton and Harlow, 2010;Doherty et al, 2012;James et al, 2011;McGee-Lawrence et al, 2015Utz et al, 2009;Wojda et al, 2012). However, some small hibernators, such as the 13-lined ground squirrel (Ictidomys tridecemlineatus) have been reported to exhibit microstructural bone loss (osteocytic osteolysis) during hibernation bouts, which has not been observed in larger hibernating animals (McGeeLawrence et al, 2011).…”
Section: Maintenance Of Musculoskeletal Properties In Hibernators Andmentioning
confidence: 99%
“…Although these studies lacked thorough quantification of a wide array of bone properties, for small mammalian hibernators there is still conflicting evidence as to whether bone loss regularly occurs during dormancy. Whereas both arctic and golden-mantled ground squirrels retain cortical bone properties and strength following hibernation (Utz et al, 2009;Wojda et al, 2012), data indicate that hibernating I. tridecemlineatus might be unable to avoid microstructural losses of cortical and trabecular bone (McGee-Lawrence et al, 2011). Nevertheless, because bone geometrical and mechanical properties do not differ significantly between hibernating and active squirrels, these animals can still perhaps activate the appropriate physiological mechanisms to maintain bone macrostructure and strength throughout hibernation in preparation for normal skeletal function during arousal.…”
Section: Mechanisms Underpinning the Inhibition Of Osteoporosismentioning
confidence: 99%
“…Like bears, marmots do not lose bone mass and strength during hibernation periods lasting 5-6 mo (Wojda et al 2012). Marmots decrease their basal metabolic rate during hibernation to 5.5% of the levels observed during periods of physical activity (Hock 1969).…”
Section: Physiological and Biochemical Zoologymentioning
confidence: 99%
“…Animals that hibernate (e.g., marmots and bears) are naturally physically inactive for extended periods (6 mo or longer) annually. However, bears, marmots, woodchucks, and ground squirrels maintain bone properties, despite these long bouts of physical inactivity (McGee et al 2007bMcGee-Lawrence et al 2009aUtz et al 2009;Doherty et al 2012;Wojda et al 2012). Hibernating mammals demonstrate remarkable resilience by having evolved physiological mechanisms that allow them to survive extreme physiological and environmental conditions for prolonged periods of time (Carey et al 2003).…”
Section: Introductionmentioning
confidence: 99%